2018
DOI: 10.1016/j.jaci.2017.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dupilumab in perennial allergic rhinitis and comorbid asthma

Abstract: Dupilumab 300 mg q2w significantly improved AR-associated nasal symptoms in patients with uncontrolled persistent asthma and comorbid PAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 30 publications
2
87
0
1
Order By: Relevance
“…Finally, Weinstein et al recently showed that dupilumab 300 mg every 2 weeks significantly improved allergic rhinitis associated nasal symptoms in patients with uncontrolled persistent asthma and comorbid perennial allergic rhinitis …”
Section: Other Biologics Which Could Be Of Interest In Children With supporting
confidence: 66%
See 1 more Smart Citation
“…Finally, Weinstein et al recently showed that dupilumab 300 mg every 2 weeks significantly improved allergic rhinitis associated nasal symptoms in patients with uncontrolled persistent asthma and comorbid perennial allergic rhinitis …”
Section: Other Biologics Which Could Be Of Interest In Children With supporting
confidence: 66%
“…Finally, Weinstein et al recently showed that dupilumab 300 mg every 2 weeks significantly improved allergic rhinitis associated nasal symptoms in patients with uncontrolled persistent asthma and comorbid perennial allergic rhinitis. 44 Considering all these results, we hypothesize that dupilumab could be interesting in children with severe eosinophilic asthma with allergic comorbidities, especially severe atopic dermatitis and allergic rhinitis, and with lung function impairment. (-34% in the tezepelumab arm vs -45.9% in the placebo arm, P < 0.02).…”
Section: Monoclonal Antibodies Directed Against Il-4 and Il-13mentioning
confidence: 94%
“…Dupilumab reduces asthma exacerbations, allows a gradual reduction in the use of OCS, and improves lung function. (101)(102)(103)(104)(105) It is administered subcutaneously, at a recommended dose of 400 mg initially, followed by 200 mg on alternate weeks. For patients using OCS or with comorbidities (atopic dermatitis, nasal polyposis, or eosinophilic esophagitis), the recommended dose is 600 mg initially, followed by 300 mg every 2 weeks.…”
Section: Other Medications For the Treatment Of Severe Asthmamentioning
confidence: 99%
“…More recently, dupilumab, a fully humanized biologic that targets the IL‐4Rα subunit to inhibit the activity of both IL‐4 and IL‐13 has been developed for airway diseases including chronic rhinosinusitis . In this regard, a double‐blind, placebo‐controlled phase IIb clinical trial of patients with uncontrolled persistent asthma and comorbid AR has demonstrated that 300 mg of dupilumab every 2 weeks as an add‐on therapy to medium‐to‐high‐dose inhaled corticosteroids + long acting beta‐agonists (ICS + LABA) significantly improved the symptoms of AR in these patients, suggesting that dupilumab add‐on therapy may have a role in nasal symptom relief for this important subgroup of patients …”
Section: Treatmentmentioning
confidence: 99%
“…57 Decreased number of ILC2s are observed in peripheral blood after nasal allergen challenge (NAC) and are positively correlated with AR symptoms in birch allergic objects irritated outside of the local birch pollen season. 58 Dupilumab Anti-IL4Rα Subcutaneous 106 activation of DC, basophils and T cells in the peripheral blood following NAC. 60 DCs from patients with AR and asthma display impaired IL-12 and IFN-α production in response to toll-like receptor (TLR) 4 and TLR9 activation, respectively, as well as impaired induction of IL-10-producing CD4 + T cells.…”
Section: Environmental Factorsmentioning
confidence: 99%